New application of heterocyclic diazonium salts. Synthesis of pyrazolo[3,4-d][1,2,3]triazin-4-ones and imidazo[4,5-d][1,2,3]triazin-4-ones - Colomer, Juan Pablo (2011)
The pyrazolo[3,4-d][1,2,3]triazin-4-ones 3 and imidazo[4,5-d][1,2,3] triazin-4-ones 4 are analogs structurally related to purines that have showed a wide and significant variety of biological activity. These compounds were synthesized by one-pot diazotization of 5-amino-1H-pyrazole-4-carbonitriles 1 and 5-amino-1H-imidazole-4-carbonitriles 2, respectively.